2017
DOI: 10.1177/1591019917740100
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular treatment outcomes using the Stroke Triage Education, Procedure Standardization, and Technology (STEPS-T) program

Abstract: Background “Door to treatment” time affects outcomes of acute ischemic stroke (AIS) patients undergoing endovascular treatment (EVT). However, the correlation between staff education and accessible technology with stroke outcomes has not been demonstrated. Objective The objective of this paper is to demonstrate the five-year impact of the Stroke Triage Education, Procedure Standardization, and Technology (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The most frequent interventions associated with improved workflow efficiency (SMD <0) included prenotification, direct‐to‐CT procedures, skipping multimodal CT, education and training, and monitoring and feedback, reinforcing the importance of their implementation in stroke rescue chain guidelines ( SI Table 5 ) . Although certain workflow practices such as prenotification and bedside tPA administration may be easily integrated into the AIS rescue chain, the implementation of interventions such as physician education and training may be limited by the resources of the participating stroke centre 16‐18 . Redesigning best‐practice guidelines for resource limiting settings and investigating the effect on temporal metrics and reperfusion rates is a promising area of future research.…”
Section: Discussionmentioning
confidence: 99%
“…The most frequent interventions associated with improved workflow efficiency (SMD <0) included prenotification, direct‐to‐CT procedures, skipping multimodal CT, education and training, and monitoring and feedback, reinforcing the importance of their implementation in stroke rescue chain guidelines ( SI Table 5 ) . Although certain workflow practices such as prenotification and bedside tPA administration may be easily integrated into the AIS rescue chain, the implementation of interventions such as physician education and training may be limited by the resources of the participating stroke centre 16‐18 . Redesigning best‐practice guidelines for resource limiting settings and investigating the effect on temporal metrics and reperfusion rates is a promising area of future research.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have concluded the benefits of physician education and feedback on improving in‐hospital procedural metrics and streamlining reperfusion therapy delivery, with a 2019 meta‐analysis concluding that physician feedback results in the greatest median reduction in treatment time (64 minutes, P = .002). Components of physician education have been incorporated into multiple trials, all of which have improved in‐hospital workflows 40,78‐80 . A 2015 network‐wide stroke improvement programme found stroke education, and regular simulation training was critical to improving median DPT by 15.5 minutes; however, this did not reach statistical significance 78 .…”
Section: In‐hospital Workflow Parametersmentioning
confidence: 99%
“…A 2015 network‐wide stroke improvement programme found stroke education, and regular simulation training was critical to improving median DPT by 15.5 minutes; however, this did not reach statistical significance 78 . A 5‐year prospective database registry concluded that the use of stroke triage education, procedural standardization and temporal feedback systems achieved significant reductions in angiography‐to‐recanalization times by 69 minutes, with significant improvements in all aspects of angiography workflow and associated clinical outcomes 80 . Reliable and transparent recording of temporal parameters in acute stroke workflow is essential in developing time metrics and quality initiatives to aim for when streamlining reperfusion therapy delivery in future.…”
Section: In‐hospital Workflow Parametersmentioning
confidence: 99%
“…The program fundamentally revolves around three interlaced principles affecting the speed and quality of care: (1) procedure workflow, (2) technologies, and (3) education. Additionally, each workflow step is recorded, using "digital objects, " or macro-enabled systems, which allow staff in the care pathway to remain connected, as stated by the American Heart Association Data Summit on the importance of integrating digital objects in modern stroke care (19,20). Prior evidence indicates the importance of these three interrelated domains (15,16,18).…”
Section: Steps-tmentioning
confidence: 99%